MODERN METHODS FOR ASSESSING THE CONDITION OF THE MUCOSUS CAVITY OF THE MOUTH AND PERIODONT - S.M. Gerashchenko; A.V. Demidov (Модели, системы, сети в экономике, технике, природе и обществе, 2023)
Background. The aim of the work is to review and analyze modern methods for assessing the condition of the oral mucosa and periodontium. Materials and methods. In order to select promising methods for assessing the condition of the oral mucosa and periodontium, a classification of methods was developed based on the underlying physical principle. An analysis of these methods was also carried out in terms of the measured parameter, invasiveness, rapidity of the method and the possibility of its use at the preclinical stage of the disease. Results. Early diagnosis of diseases of the oral mucosa and periodontal disease in the preclinical stage, due to the reversibility of processes, increases the chances of complete recovery. This is relevant due to the high risk of malignant degeneration of damaged soft tissues of the mucosa against the background of inflammatory diseases. Conclusions. The advantages of electrochemical methods of diagnostics are revealed.